Gastritis and Gastric Ulcers in Working Dogs - Davis, Michael S.; Williamson, Katherine K. (Frontiers in Veterinary Science, 2016)
Gastritis and gastric ulcers are an important cause of morbidity and mortality in canine athletes. Although the majority of scientific work on this condition has been performed in ultraendurance racing sled dogs, this condition has been identified in other canine athletes including sled dogs competing in shorter events and dogs performing off-leash explosive detection duties. The cause of the syndrome is unknown, but current hypotheses propose a link between exercise-induced hyperthermia and loss of gastric mucosal barrier function as an early event in the pathogenesis. Treatment is focused on prevention of clinical disease using acid secretion inhibitors such as omeprazole, which has excellent efficacy in controlled clinical studies.